Exploring the role of school principals as instructional leaders Improving learner academic performance in Johannesburg South District Primary Schools - Zuma, Chuma (University of the Witwatersrand, Johannesburg, 2024)
This study explores the role of the principal as an instructional leader in four successful primary schools in the township. It examines instructional strategies used by principals of the four schools that may help to raise learner achievement and explores how these successful leaders use leadership styles and management approaches to improve learner academic performance in their schools. Sixteen participants were involved in this study. They include: four principals, four deputy principals, four departmental heads (DHs) and four teachers from the four schools. Data was collected using qualitative approaches; this being achieved through individual semi-structured interviews. The study found that the critical instructional leadership approaches used by these principals were promoting teamwork, active participation, collective decision making, sharing of responsibilities, collaboration and distribution of tasks amongst multiple leaders. The teachers and members of the school management team (SMT) confirmed the claims made by the principals. Data also indicated that the principals relied on a combination of different leadership styles and efficient and effective management approaches with their subordinates to save the enthusiastic implementation of instructional approaches that help to yield good learner results. The study suggests that there might be a strong link between leadership styles and learner performance. The data also suggests that the relevant leadership styles can contribute to institutional spirit against the main challenges which tend to depress performance in many schools in similar circumstances. The study makes specific recommendations for a broad-based research agenda to examine factors which contribute to success in schools operating in challenging circumstances.
A research report submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Leadership; management; instructional leadership; learner outcomes; SDG-4: Quality education